Relasi Kuasa dan Pengelolaan Kesehatan Reproduksi Perempuan Pekerja Seks di Pantai Gunungkidul - Victoria Sundari Handoko (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2013)
Essentialist perspective with emphasis on binary opposition is still dominant in society. In general they assess human behavior in terms of â€œrightâ€ and â€œwrongâ€ or â€œnormalâ€ and â€œabnormalâ€. This implies the attached stigmatization of women sex workers as people who behave â€œwrongâ€ or â€œnot normalâ€ and the source of societyâ€™s illness. Several central and local government policies make womenâ€™s bodies of sex workers as objects, such as Law No 44, 2008, concerning pornography, also some regional regulations such discriminatory regulation on prohibition of prostitution or antiimmorality. Discrimination by the rules and gender injustice arise from the relation of sex workers with legal institutions, government, tourism industry, and health is a form of dominance of power over the body of sexual workers. It becomes an interesting study because it implies women that do not have authority over their own body. This study was conducted to analyze the relations of power and management of reproductive health and sexuality female sex workers in Gunungkidul Beach. The research used qualitative approach and the data collection techniques were interviews and observation. The results showed that sex workers can be grouped into two categories: first, sex workers who stay in the hotel and secondly, sex workers who were outside the hotel (food stalls and homes around the coast). The differences in the characteristics of sex workers led to the differences of power relations, meanwhile the differences in the management of reproductive health and sex were caused by the presence or absence of reproductive health and sex education that have been.